Structural characterization of recombinant bovine Goα by spectroscopy and homology modeling - (:unkn) unknown (My University, 2011)
Go, a member of heterotrimeric guanine nucleotide-binding proteins, is the most abundant form of G protein in the central and peripheral nervous systems. Goα has a significant role in neuronal development and function but its signal transduction mechanism remains to be clarified. In this study, the bovine Goα subunit was overexpressed and purified into homogeneity. Its activity was studied using [ 35S] GTPγS binding, intrinsic fluorescence and BODIPY assays. The secondary structure was determined by both FTIR and CD spectroscopy as 42.3% α-helix, 13.4% β-sheet and 24.3% β-turn. A theoretical structure model was constructed. The structure from homology modeling is in very good agreement with the crystal structure of mouse Goα subunit except for the loop between αB-αC helices. This model was docked to the mouse RGS16 molecule. T117 on the αB-αC loop of Goα interacted with K172 on RGS16 as opposed to the T117 and K164 interaction in mouse. © 2011 - IOS Press and the authors. All rights reserved.
Keywords: circular dichroism; FTIR spectroscopy; Goα protein; homology modeling